Empirical and Theoretical Analysis of Particle Diffusion in Mucus - Cobarrubia, Antonio; Tall, Jarod; Crispin-Smith, Austin; Luque, Antoni (Frontiers in Physics, 2021)
Mucus is a complex fluid that coats multiple organs in animals. Various physicochemical prop- erties can alter the diffusion of microscopic particles in mucus, impacting drug delivery, virus infection, and disease development. The simultaneous effect of these physicochemical properties in particle diffusion, however, remains elusive. Here, we analyzed 106 published experiments to identify the most dominant factors controlling particle diffusion in mucus. The effective diffusion— defined using a one-second sampling time window across experiments—spanned seven orders of magnitude, from 10^5 to 10^2 μm^2/s. Univariate and multivariate statistical analyses identified the anomalous exponent (the logarithmic slope of the mean-squared displacement) as the strongest predictor of the effective diffusion, revealing an exponential relationship that explained 89% of the variance. A theoretical scaling analysis revealed that the stronger correlation of the anomalous exponent over the generalized diffusion constant occurs for sampling times two orders of magnitude larger than the characteristic molecular (or local) displacement time. This result predicts that, at these time scales, the molecular properties controlling the anomalous exponent, like particle-mucus unbinding times or particle-to-mesh size ratio—which depend on the underlying subdiffusion’s mechanism—would be the most relevant physicochemical factors involved in the passive microrhe- ology of particles in mucus. Our findings contrast with the fact that only one-third of the studies measured the anomalous exponent, and most experiments did not report the associated molecular properties predicted to dominate the motion of particles in mucus. The theoretical foundation of our work can be extrapolated to other systems, providing a guide to identify dominant molecular mechanisms regulating the mobility of particles in mucus and other polymeric fluids.